METODE UNJUK GIGI DALAM PEMBELAJARAN IPS: Studi Kasus di Sekolah Master, Kota Depok, Jawa Barat - Fenty, Annisa Eka; Sujarwo, Sujarwo (Edukasi IPS, 2018)
This study aims to find out the learning process of IPS with a method of showing off MASTER, Depok, West Java. Method used in this research is qualitative method. The data source comes from primary and secondary data. Technique of data collecting done through observation, interview, and documentation. Observation is done by viewing, observing, and recording IPS learning process with show method in class VIII. Interviews were conducted with the principal, IPS school tutor MASTER and MASTER school students. Documentation is done by plowing the image in the form of photos related to the research. The results of this study indicate that the method of showing in the MASTER school, by way of conditioning the class in the learning that is in the plane. The method of showing off consists of a collecting stage, flying and joy. The conclusion of this research is that the method of showing in IPS learning in MASTER's school has been effective. Teacher becomes a good facilitator. Teachers use methods of showing that are able to attract students' interest, attention and responses in learning. Students have an interest in the method of showing. Student interest in the method of performance makes the students' learning achievement increases.